The Role of Islamic Education in Shaping the Digital Ethics of Alpha Generation - Samhudi Samhudi; Ahmad Sani (Kuttab: Jurnal Ilmu Pendidikan Islam, 2026)
The rapid development of digital technology brings new challenges to the character building of the Alpha generation growing up in a digital ecosystem; the Alpha generation is vulnerable to the negative influence of cyberspace, such as moral degradation. This study aims to examine how Islamic Education shapes the digital ethics of the alpha generation and the strategic steps it takes to build the alpha generation's character. Through a qualitative approach with a literature study method, this study found that Islamic Education plays a role in building awareness of digital ethics through instilling awareness of Islamic morals in doing activities on social media, preventing cyberbullying and hate speech behavior by instilling Islamic values, teaching the concept of trust in the use of digital media, and developing a critical attitude towards digital information. In addition, strategic steps that can be implemented include integrating digital ethics material into the Islamic Education curriculum, optimizing teachers' roles as moral mentors, and collaborating with parents and communities to monitor children's use of digital technology.